Fracture liaison services: improving outcomes for patients with osteoporosis - Walters S; Khan T; Ong T; Sahota O (Clinical Interventions in Aging, 2017)
Samuel Walters,1 Tanvir Khan,2 Terence Ong,3,4 Opinder Sahota3 1East Midlands Major Trauma Centre, Queens Medical Centre, Nottingham University Hospitals NHS Trust, 2Department of Orthopaedics, Trauma and Sports Medicine, University of Nottingham, 3Department for Healthcare of Older People, Queens Medical Centre, Nottingham University Hospitals NHS Trust, 4Division of Rehabilitation and Ageing, University of Nottingham, Nottingham, UK Abstract: Fragility fractures are sentinels of osteoporosis, and as such all patients with low-trauma fractures should be considered for further investigation for osteoporosis and, if confirmed, started on osteoporosis medication. Fracture liaison services (FLSs) with varying models of care are in place to take responsibility for this investigative and treatment process. This review aims to describe outcomes for patients with osteoporotic fragility fractures as part of FLSs. The most intensive service that includes identification, assessment and treatment of patients appears to deliver the best outcomes. This FLS model is associated with reduction in re-fracture risk (hazard ratio [HR] 0.18–0.67 over 2–4 years), reduced mortality (HR 0.65 over 2 years), increased assessment of bone mineral density (relative risk [RR] 2–3), increased treatment initiation (RR 1.5–4.25) and adherence to treatment (65%–88% at 1 year) and is cost-effective. In response to this evidence, key organizations and stakeholders have published guidance and framework to ensure that best practice in FLSs is delivered. Keywords: fracture liaison service, fractures, fall, osteoporosis, aged